Religião e política no Brasil, Uruguai e Argentina: sobre uma pluralidade transnacional = Religion and politics in Brazil, Uruguay and Argentina : about a transnational plurality - Meirelles, Mauro (Ciencias sociales y religión, 2016)
his text deals with religion and politics in the cisplatincontext. In this sense, it discusses and opposes the idea of plurality and religious diversity based on existing statistical data about the three countries and the representations that both Catholic and Evangelicals and Afro-Brazilians have about these two fields, pointing to the existence of certain views and ways of Being, and being in the world that check the statistical data showing that, from the theological and teleological point of view, this announced plurality and diversity is not as plural as it is meant to be.